Development of interpretive criteria and quality control limits for macrolide and clindamycin susceptibility testing of Streptococcus pneumoniae. - Jorgensen, J H (1996)
A six-laboratory collaborative study was conducted to develop MIC and zone diameter quality control limits and interpretive criteria for antimicrobial susceptibility testing of Streptococcus pneumoniae with azithromycin, clarithromycin, dirithromycin, and clindamycin. The MICs of all of the agents plus erythromycin for 302 clinical isolates of pneumococci that had been selected with an emphasis on resistant strains were determined by use of the National Committee for Clinical Laboratory Standards (NCCLS)-recommended broth microdilution procedure. The zone diameters of the isolates were also determined for the same agents except erythromycin by the NCCLS disk diffusion test procedure. Repeated testing of S. pneumoniae ATCC 49619 with different sources and lots of media and disks allowed development of MIC and zone diameter quality control ranges for these agents. Interpretive criteria for the MIC of azithromycin were established and were as follows: susceptible, < or = 0.5 microgram/ml; intermediate, 1 microgram/ml; and resistant, > or = 2 micrograms/ml. The interpretive criteria advocated for the MICs of clarithromycin and clindamycin were as follows: susceptible, < or = 0.25 microgram/ml; intermediate, 0.5 microgram/ml; and resistant, > or = 1 microgram/ml. Comparison of MICs and disk diffusion zone diameters led to the development of interpretive criteria for the zone diameters for azithromycin, clarithromycin, and clindamycin that correlated well with these MIC breakpoints. Testing of this organism collection also led to the reestablishment of the erythromycin MIC breakpoints as being identical to those of clarithromycin, which resulted in equivalent cross-susceptibility and cross-resistance for the three macrolides that are currently marketed in the United States. Thus, the susceptibility of pneumococci to azithromycin and clarithromycin can be predicted accurately by testing only erythromycin in clinical laboratories. This recommendation, as well as the interpretive and quality control criteria that are described, have been accepted by NCCLS and are included in the latest NCCLS susceptibility testing guidelines.